Laddu Paida Hua - Chumchum (Karachi Oxford University Press, 2015)
Laddu is born is about the celebration of birth of a baby monkey called Laddu. This book closely follows the style of Miffy books developed by Dutch author/illustrator Dick Bruna.
Includes Colored Illustrations
Keywords: Children : Stories